Validation of an antiviral assay method for quantifying IFN-α5 activity in macaque and human serum. (February 2013) - Arbillaga, Leire; Murillo-Arbizu, Mayte; González, Iranzu; Gil, Ana G; Vettorazzi, Ariane; González-Peñas, Elena; Larrea, Esther; de Cerain, Adela López
Background: IFN-α5 has been demonstrated to induce stronger signaling and higher expression of antiviral genes than IFN-α2, which is the current treatment in chronic viral hepatitis. However, there is no specific and validated quantification method in order to conduct kinetic studies as part of the preclinical and clinical evaluation for regulatory purposes.Results: A novel integration of an antiviral assay against the cytopathic effect of the encephalomyocarditis virus in HeLa cells with a very sensitive method for assay processing – the Vialight ® Plus assay – is presented for IFN-α5 activity quantification. The bioassay has been validated in macaque and human serum and it has been demonstrated to be selective, precise and accurate.Conclusion: The validated bioassay meets suitable acceptance criteria for these types of biological assays.